(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2018)
Background: Lifestyle diseases namely Diabetes Mellitus, Hyperlipidemia, Hypertension, can lead to life threatening condition known as Chronic Kidney Disease (CKD). It is a condition in which the kidneys are no longer able to maintain the normal composition of blood and renal function get completely hampered. Nearly ten percent of India’s 1.24 billion people suffer from Chronic Kidney Disease, a disease in which the kidney slowly loses function and fails. Objective: The present study was conducted to screen dialysis patients for the prevalence of malnutrition during their stay in hospital through a tool namely Subjective Global Assessment (SGA). Methodology: SGA is a tool for screening malnutrition in a wide variety of health care setting. It is a valid and clinically useful measure of protein-energy nutritional status in maintenance dialysis patients. The study was carried out on 60 adults with minimum age of 18years. Results: Nutritional status assessments of patients on Haemodialysis using SGA Tool were found to be moderately malnourished (89%), 10% are severely malnourished and remaining was well nourished. Conclusion: It was concluded that the cause behind the poor nutritional status of majority is multi-factorial. The patients irrespective of age and gender were not able to meet their nutrient requirement as per the Guidelines for Maintenance Haemodialysis in India. India’s CKD problems have reached epidemic proportions, thus it is suggested that emphasis on nutrition counselling of such patients is very important to sustain a better livelihood.